Fluoroscopically-guided epidural blood patch for spontaneous intracranial hypotension - Manish Shah; David M Giampetro; Paul Kalapos; Julia C Caldwell (Wolters Kluwer Medknow Publications, 2015)
We present three patients with spontaneous intracranial hypotension who failed conservative treatment and were treated with image-guided epidural blood patch close to the cerebrospinal fluid (CSF) leak site. Each patient achieved significant long-term improvement of clinical symptoms and CSF leak related image findings.